Procura-se Denilto Gomes: um caso de desaparecimento no jornalismo cultural - Camargo, Andréia Vieira Abdelnur (2008)
Relations between cultural journalism and Brazilian dance have quite a singular nature. Due to the non-existence of a specialized segment in dance publications, along the years, cultural journalism had to fulfill the function of historian and archivist of dance. So, the acting of cultural jornalism when it was published (for the type of text that was produced) and when it wasn t published (for collaborating so that the event would not be documented) it was always accompanied by scattered, episodic publications and geographical limited reachness. This thesis uses the action of the cultural journalism regarding the work of the dancer Denilto Gomes as a case study to discuss the function of media in the culture of dance in Brazil. The impact produced by Denilto Gomes s creation process allows a critical reading on the ways of acting of cultural journalism, to his time, when they produced the disappearance phenomenon of this artist. The first chapter describes the negligence of cultural journalism regarding dance artists, in special those who developed more law-breaking experiences, through evolutionary theories and the critical theories of culture and media. The second chapter is based upon the Corpomídia Theory by Helena Katz and Christine Greiner, in articulation to the General System Theory and to the Cognitive Sciences. It investigates how the performances developed by Denilto Gomes could operate the construction of a language in dance, in all his career. The last chapter, through the evolutionary theories, deals with the hypothesis by which the language conceived during the dancer s career survives because of multiple replications, through the contact that he had with other artists and through other forms of registers about his work. So, the role of cultural journalism as a regulator of information transmission begins to be treated in a more wide-ranging context. This helps understanding that Denilto s work almost ignored by the mass media left continuators, even if in scattered dimension